Perbandingan Open dan Closed Drainage Pada Tatalaksana Abses Leher Dalam Multipel Di RSUP DR Mohammad Hoesin Palembang - Yanti, Lisa Apri; Kusuma, Aji; Irfanuddin, Irfanuddin (Oto Rhino Laryngologica Indonesiana, 2025)
Background: Management of deep neck abscesses includes evacuation of pus from the abscess location, which can generally be divided into open drainage and closed drainage. Data regarding their comparison in deep neck abscesses are still inadequate. Purpose: To compare open and closed drainage in the management of patients with multiple deep neck abscesses. Method: Observational research using a cross-sectional design on 71 subjects diagnosed with multiple deep neck abscesses at RSUP Dr. Mohammad Hoesin Palembang who underwent drainage. Result: 37 subjects underwent open drainage (52.1%) and 34 underwent closed drainage (47.9%). A statistically significant difference between the open and closed drainage groups was observed in length of stay, duration until drain removal, days until the pus changed color and pus drained per day. Conclusion: Open drainage had more favorable outcomes compared to closed drainage. Comorbid factors were found to be affecting the efficacy of abscess drainage.